Dynamic effect on turnouts of cars having wheelsets with thin flanges - B. E. Glyuzberg; M. I. Titarenko; E. A. Timakova; A. A. Savchenko; S. V. Kuznetsov; А. M. Kalachev (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
Geometrical parameters of the “wheelset—rail track” system are mutually related. Currently, a very topical issue is the question of a possible adjustment of the regulatory framework in the “wheelset—rail track” system in order to take into account the actual state of the track, turnouts and wheel park on the railway network.Any changes made in order to reduce the maintenance of wheelsets or tracks are possible only when the safety of train traffic is unconditionally ensured.The most difficult problem in determining the possibility of changing the standard for the minimum thickness of the flange of car wheels is the problem of passing the turnouts. In the event of an incorrect setting of the standard for the minimum thickness of the flange of the wheels, the passage of carriage along the turnout can be accompanied by unfavorable and even dangerous phenomena. The most dangerous of these are wheel strikes against retracted point rail, ramps on the crosspiece at large angles, and strikes against counter rails. These phenomena cause both disruptions in the geometry of the rail track of the turnout switches and crosses, and fractures of the elements of the turnouts. They should be excluded.Calculations and modeling based on the results of the study of statistical distributions of dimensions obtained by mass measurements on the railway network are the basis for the assignment of norms and tolerances in the “wheelset—rail track” system. The results obtained in the calculations should be verified by dynamic-strength tests directly on the track.The article discusses the results of dynamic and strength tests to determine the effect of cars with different geometric parameters of wheelsets on turnouts with pre-formed average network and maximum permissible dimensions of the rail track parameters on the turnout and in the cross node. The minimum thickness of the wheel flange in the tests was 21.5 mm. The carriages of the test train during the test trips were loaded to the maximum permissible size and in an empty state. The tests were carried out at the Test Center of the JSC “VNIIZhT”.